2011
DOI: 10.4314/gmj.v44i3.68892
|View full text |Cite
|
Sign up to set email alerts
|

A two-year review of uterine rupture in a regional hospital

Abstract: SUMMARYBackground: Uterine rupture causes high maternal and neonatal mortality in many rural setting in the world. Further studies might provide specific interventions to reduce the high prevalence. Objective: To determine the frequency, causes, clinical presentation, management and outcome of uterine rupture Setting: Department of Obstetrics and Gynaecology, Upper West Regional Hospital, Wa, Ghana. Design: Retrospective descriptive study. Method: A descriptive study of cases of ruptured uterus in the Regional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
51
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(67 citation statements)
references
References 14 publications
13
51
3
Order By: Relevance
“…7,12 In Nigeria , Ghana, Ethiopia and Bangladesh, incidence of about 75% of cases of uterine rupture were associated with unscarred uterus. 4,7,13 53.83% of women with uterine rupture underwent rent repair in our study, which was comparable to other Indian studies. Most of the studies from African countries and few from Pakistan showed that significant number of rupture uterus cases managed by repair with bilateral tubal ligation.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…7,12 In Nigeria , Ghana, Ethiopia and Bangladesh, incidence of about 75% of cases of uterine rupture were associated with unscarred uterus. 4,7,13 53.83% of women with uterine rupture underwent rent repair in our study, which was comparable to other Indian studies. Most of the studies from African countries and few from Pakistan showed that significant number of rupture uterus cases managed by repair with bilateral tubal ligation.…”
Section: Discussionsupporting
confidence: 87%
“…Among the developing countries, the incidence varied in 1:124 (0.8%) in Ghana, 0.74% in Pakistan, 0.9% in Nepal and 2.8% in Ethiopia. [4][5][6][7] The incidence in developed countries is recorded at least ten times lower (0.035%). This wide variation in incidence is due to socio-economic factors, cultural practices and lack of access between to antenatal and intrapartum care.…”
Section: Discussionmentioning
confidence: 99%
“…12 But in developing countries late symptoms and signs are the ones that clinch the diagnosis. 15 In 84% of our subjects, the rupture of the uterus was complete. In other studies, complete rupture was noted in 66% by Sahu L, 57.1% by Dhaifalah I and 88% by Sunitha K. 8,20,6 In 52%, the tear involved the previous uterine scar or the anterior wall.…”
Section: Discussionmentioning
confidence: 79%
“…All 25 women required blood transfusion, which is not the case in most of the studies including those from African countries. 5,8,15 The reason for such high rates of blood transfusion in our women could be that most of them start the pregnancy with anaemia. Haemoglobin at time of admission was less than or equal to 8 gm% in 56% of the women.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation